2007
DOI: 10.1016/j.foodchem.2007.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive properties of the medicinal mushroom Leucopaxillus giganteus mycelium obtained in the presence of different nitrogen sources

Abstract: Leucopaxillus mushroom species are used in the chemical industry for extraction of clitocybin antibiotic and particularly the edible mushroom Leucopaxillus giganteus can be found in Northeast Portugal. Nevertheless, the production of its mycelium for pharmacological applications has not been explored. Herein, the mycelium obtained in the presence of four different nitrogen sources was investigated with regard to phenol production and antimicrobial and antioxidant properties. Phenol concentration increased alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 28 publications
(22 reference statements)
4
31
2
Order By: Relevance
“…The results show that species harvested from the wild exhibited higher correlation values with the phenolic component than those obtained by cultivation in a laboratory greenhouse. Previous studies confirmed these differences indicating that the presence of polyphenolic compounds is negatively correlated with the antioxidant activities (36). It has been shown that the principle component is the main contributor to the causal effect (37).…”
Section: Resultsmentioning
confidence: 71%
“…The results show that species harvested from the wild exhibited higher correlation values with the phenolic component than those obtained by cultivation in a laboratory greenhouse. Previous studies confirmed these differences indicating that the presence of polyphenolic compounds is negatively correlated with the antioxidant activities (36). It has been shown that the principle component is the main contributor to the causal effect (37).…”
Section: Resultsmentioning
confidence: 71%
“…(Cheung 1998;Manzi and Pizzoferrato 2000;Bobek et al 2001;Mau et al 2001;Mau et al 2002). These papers covered species of the genera Lentinus, Hericium, Grifola, Flammulina, Pleurotus, Tremella, Boletus, Agrocybe and Leucopaxillus which occur in forest areas from the most diverse climates around the world (Gunde-Cimerman 1999; Kues and Liu 2000;Manzi et al 2004;Carbonero et al 2006; Barros et al 2007; Barros et al 2008). Interspecific differences in health beneficial functions of various species of mushrooms were examined by Rosado et al (2002) and Rhee et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of L. edodes extracts to improve oral health has also been extensively researched, since it showed a strong bactericidal effect upon Streptococcus mutans, which is strongly implicated in dental caries and tooth decay [53,54]. The mycelium of Leucopaxillus giganteus (methanolic extract) presented antimicrobial capacity, inhibiting only gram-positive bacteria and, in decreasing order, Staphylococcus aureus > Bacillus cereus > Bacillus subtilis [55]. The authors stated that the most promising nitrogen source to produce mushrooms with an increased content in bioactive compounds that inhibit gram-positive bacteria growth was (NH 4 ) 2 HPO 4 .…”
Section: Mushroom Extracts With Antimicrobial Activitymentioning
confidence: 99%